Respuesta :

-7 _D_

[tex]\frac{3}{2}[/tex] _A_

1 _C_

[tex]\frac{-1}{4}[/tex] _B_

_A_ [tex]\frac{y^{2} -2y+1}{2y-3}[/tex]

_B_ [tex]\frac{y(y+5)}{4y+1}[/tex]

_C_ [tex]\frac{5y^{2}-6y+1 }{-5(y-1)}[/tex]

_D_ [tex]\frac{y^{2}-y-6 }{-2(y+7)}[/tex]


Ver imagen dakotacsey03

Answer:

-7     →     [tex]\dfrac{y^2-y+6}{-2(y+7)}[/tex]

3/2  →      [tex]\dfrac{y^2-2y+1}{2y-3}[/tex]

1      →      [tex]\dfrac{5y^2-6y+1}{-5(y-1)}[/tex]

-1/4  →      [tex]\dfrac{y(y+5)}{4y+1}[/tex]

Step-by-step explanation:

We need to find the nonpermissible replacements for y.

Equate the denominator of each expression equal to 0, to find the nonpermissible replacements for y.

First expression is

[tex]\dfrac{y^2-2y+1}{2y-3}[/tex]

Equate (2y-3) equal to 0.

[tex]2y-3=0[/tex]

Add 2 on both sides.

[tex]2y=3[/tex]

Divide both sides by 3.

[tex]y=\dfrac{3}{2}[/tex]

Therefore, 3/2 is the nonpermissible replacements for y.

Second expression is

[tex]\dfrac{y(y+5)}{4y+1}[/tex]

Equate (4y+1) equal to 0.

[tex]4y+1=0[/tex]

[tex]4y=-1[/tex]

[tex]y=-\dfrac{1}{4}[/tex]

Therefore, -1/4 is the nonpermissible replacements for y.

Third expression is

[tex]\dfrac{5y^2-6y+1}{-5(y-1)}[/tex]

Equate -5(y-1) equal to 0.

[tex]-5(y-1)=0[/tex]

[tex]y-1=0[/tex]

[tex]y=1[/tex]

Therefore, 1 is the nonpermissible replacements for y.

Fourth expression is

[tex]\dfrac{y^2-y+6}{-2(y+7)}[/tex]

Equate -2(y+7) equal to 0.

[tex]-2(y+7)=0[/tex]

[tex]y+7=0[/tex]

[tex]y=-7[/tex]

Therefore, -7 is the nonpermissible replacements for y.

ACCESS MORE